Cover Image. (10th September 2018) - Wang, Jun; Zhang, Chunyan; Yang, Hao; Mou, Chengxiang; Mo, Li; Luo, Peng
Abstract : The cover image, by Jun Wang et al., is based on the Research Article Plant community ecological strategy assembly response to yak grazing in an alpine meadow on the eastern Tibetan Plateau, https://doi.org/10.1002/ldr.3050 .